Experimental Study on Fresh and Hardened Properties of Concrete with Fine Aggregate Replacement by Manufactured Sand a Review - Pooja Raj; Dharmendra Prajapati (International Journal of Scientific Research in Civil Engineering, 2025)
The growing demand for natural river sand as a fine aggregate in concrete production has led to over-exploitation of riverbeds, causing environmental concerns such as soil erosion and depletion of aquatic ecosystems. Consequently, there has been a significant shift toward finding sustainable alternatives to natural sand. One such alternative is Manufactured Sand (M-sand), which is produced by crushing granite stone and can serve as a viable replacement for river sand in concrete. This study explores the potential of M-sand as a substitute for natural river sand in the production of M40 grade concrete. The primary objective of this research is to evaluate the impact of different proportions of M-sand on the mechanical and durability properties of concrete. In this study, M-sand was used as a partial replacement for river sand in varying proportions, ranging from 0% to 100% in increments of 10%. The mix design was based on the IS: 10262 – 1982 standard, and various concrete tests were performed to assess its workability, compressive strength, splitting tensile strength, flexural strength, and water absorption. Ordinary Portland Cement (OPC) 53-grade was used in the mix along with crushed granite as coarse aggregates. The study included an investigation of the effect of M-sand on the workability of fresh concrete and the mechanical strength of hardened concrete, including compressive, tensile, and flexural strength, to understand the structural performance of the concrete. In this paper presenting review of literatures
Keywords: Manufactured Sand (M-sand); River Sand; Concrete; M40 Grade Concrete; Mechanical Properties; Durability; Compressive Strength; Tensile Strength; Flexural Strength; Workability